Safety study of cannabidiol products in healthy dogs - Bookout, William; Dziwenka, Margitta; Valm, Kaiti; Kovacs-Nolan, Jennifer (Frontiers in Veterinary Science, 2024)
The tolerability of different cannabinoids given orally to dogs was evaluated in a randomized, non-blinded, negative controlled, parallel design 90-day repeat dose study with a 14-day recovery period. Healthy beagles (16 males and 16 females) were randomized into four treatment groups and treated with either medium chain triglyceride oil as the control or one of the following: broad spectrum cannabidiol, broad spectrum cannabidiol with cannabigerol, or broad spectrum cannabidiol with cannabidiolic acid at 5 mg total cannabinoids/kg body weight/day. Animals were observed daily with detailed clinical examinations conducted weekly. Animals were monitored for an additional two weeks after dosing. Body weights, food consumption and clinical pathology evaluations were included in the study. Cannabinoids were well tolerated when healthy male and female beagles were dosed for 90 consecutive days. Annual post-market surveillance data for hemp-derived supplement products sold for use in dogs from 2010 to 2023 (partial year) shows that the rate per 1 million administrations sold is 2.10 for adverse events and 0.01 for serious adverse events. Based on the results of this study, other published studies, and data from extensive post-market surveillance, hemp-derived cannabinoids are well tolerated in healthy dogs at a dose of 5 mg/kg body weight/day.